Hsp70.1 carbonylation induces lysosomal cell death for lifestyle-related diseases - Yamashima, Tetsumori; Seike, Takuya; Oikawa, Shinji; Kobayashi, Hatasu; Kido, Hidenori; Yanagi, Masahiro; Yamamiya, Daisuke; Li, Shihui; Boontem, Piyakarn; Mizukoshi, Eishiro (Frontiers in Molecular Biosciences, 2023)
Alzheimer’s disease, type 2 diabetes, and nonalcoholic steatohepatitis (NASH) constitute increasingly prevalent disorders. Individuals with type 2 diabetes are well-known to have an increased risk for developing Alzheimer’s disease. Although the pathogenesis of each disease is multifactorial and the causal relation remains poorly understood, reactive oxygen species (ROS)-induced lipid and protein oxidation conceivably plays a common role. Lipid peroxidation product was recently reported to be a key factor also for NASH, because of inducing hepatocyte degeneration/death. Here, we focus on implication of the representative lipid-peroxidation product ‘hydroxynonenal’ for the cell degeneration/death of brain, pancreas, and liver. Since Hsp70.1 has dual functions as a chaperone protein and lysosomal stabilizer, hydroxynonenal-mediated oxidative injury (carbonylation) of Hsp70.1 was highlighted. After intake of high-fat diets, oxidation of free fatty acids in mitochondria generates ROS which enhance oxidation of ω-6 polyunsaturated fatty acids (PUFA) involved within biomembranes and generate hydroxynonenal. In addition, hydroxynonenal is generated during cooking deep-fried foods with vegetable oils especially containing linoleic acids. These intrinsic and exogenous hydroxynonenal synergically causes an increase in its serum and organ levels to induce Hsp70.1 oxidation. As it is amphiphilic; being water-soluble but displays strong lipophilic characteristics, hydroxynonenal can diffuse within the cells and react with targets like senile and/or atheromatous plaques outside the cells. Hydroxynonenal can deepen and expand lysosomal injuries by facilitating ‘calpain-mediated cleavage of the carbonylated Hsp70.1’. The unique anatomical, physiological, and biochemical components of each organ contribute to its specific disease; however, there should be a common cascade of the cell degeneration/death which is brought by hydroxynonenal. This review aims to implicate hydroxynonenal-mediated Hsp70.1 carbonylation for lysosomal membrane permeabilization/rupture and the resultant cathepsin leakage for inducing cell degeneration/death. Given the tremendous number of worldwide people suffering lifestyle-related diseases, it’s valuable to consider how ω-6 PUFA-rich vegetable oils is implicated for the organ disorder.